Urgensi Penguasaan Pragmatik bagi Siswa Sekolah Dasar dalam Meningkatkan Keterampilan Berbahasa - Ilfa Trijulia; Melva Zainil (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the urgency of mastering pragmatics for elementary school students in improving language skills. Pragmatics is a branch of linguistics that studies the use of language in social contexts and its influence on effective communication. This study is important because good pragmatics skills can help students communicate appropriately and effectively according to the social context. The method used is a literature review of various relevant sources regarding pragmatics and its application in language learning in elementary schools. The results of the study show that mastery of pragmatics has an important role for elementary school students, including: (1) improving the ability to communicate effectively and according to context; (2) developing social skills in interaction; (3) helping to understand the implied meaning in oral and writtencommunication; (4) improving the ability to interpret text comprehensively; and (5) being the foundation for the development of critical literacy. The implementation of pragmatics learning in elementary schools can be done through various approaches, such as contextual learning, role play, simple conversation analysis, and project-based learning. This study recommends the need to integrate pragmatics aspects in the Indonesian language learning curriculum in elementary schools to prepare students to become effective communicators in various social contexts.